Outcome of Pcnl in Proximal Ureteric Stone: A Comparative Study With Laparoscopic Retrieval (Bangladesh Journal of Urology, 2020)
A hundred-percent stone clearance was achieved in a hospital based prospective clinical trial in which 60 cases of upper ureteric stone were selected by purposive sampling for percutaneous nephroureterolithotomy & Laparoscopic ureterolithotomy between December 2012 and June 2014 in BSMMU. The mean age of the patients was 40.53±11.71 (19-61) and 41.23±10.76 (20-59) years old in PCNUL and LUL groups, respectively. The mean stone size in PCNUL group was 1.88±0.39 (1.06-2.45) cm and in LUL group was 1.97±0.42 (1.20-2.60) cm. The duration of the operations were 94.13 ± 17.34 (75-140) minutes, and 121.43 ± 19.91 (90-167) minutes (P =0.001); and the average hospital stay days were 3.73 ± 1.20 (3-8) and 4.80 ± 1.71 (3-9) days (P = 0.017) in groups PCNUL and LUL, accordingly. The mean Hb decrease in PCNUL group was 1.16±0.35 mg/dL and in LUL group was 0.77±0.31 mg/dL (P =